2013
DOI: 10.1094/mpmi-09-12-0208-r
|View full text |Cite
|
Sign up to set email alerts
|

Differential Regulation ofSalmonellaTyphimurium Genes Involved in O-Antigen Capsule Production and Their Role in Persistence Within Tomato Fruit

Abstract: Enteric pathogens, including non-typhoidal Salmonella spp. and enterovirulent Escherichia coli, are capable of persisting and multiplying within plants. Yet, little is still known about the mechanisms of these interactions. This study identified the Salmonella yihT gene (involved in synthesis of the O-antigen capsule) as contributing to persistence in immature tomato fruit. Deletion of yihT reduced competitive fitness of S. enterica sv. Typhimurium in green (but not ripe, regardless of color) tomato fruit by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
28
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 32 publications
2
28
0
Order By: Relevance
“…The capacity of S. enterica (and other enteric pathogens) to readily multiply within plant tissues led to the hypothesis that persistence on plants is a part of the Salmonella life cycle, serving as reservoirs prior to reinfection of the preferred animal hosts (2)(3)(4)(5). Several studies have dissected the molecular basis of plant-Salmonella interactions (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). However, the entire complement of genetic functions required for plant colonization by Salmonella is not yet known.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The capacity of S. enterica (and other enteric pathogens) to readily multiply within plant tissues led to the hypothesis that persistence on plants is a part of the Salmonella life cycle, serving as reservoirs prior to reinfection of the preferred animal hosts (2)(3)(4)(5). Several studies have dissected the molecular basis of plant-Salmonella interactions (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). However, the entire complement of genetic functions required for plant colonization by Salmonella is not yet known.…”
mentioning
confidence: 99%
“…It involves major changes in the bacterial transcriptome and requires genes involved in amino acid biosynthesis and transport, cellulose production, fimbriae, regulators, and surface structures (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Some of the same mechanisms were involved in the colonization of both vegetative and reproductive tissues on different plant species.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A genome-wide screen using Salmonella enterica serovar Typhimurium identified a number of metabolic and regulatory genes induced during growth in tomatoes but did not demonstrate genes required for bacterial survival in this environment (20). Further work in this area showed that the O-antigen portion of bacterial lipopolysaccharide is importance for Salmonella survival in tomatoes (21), as it is in animal hosts.…”
mentioning
confidence: 99%
“…The FabH gene was upregulated most strongly in immature tomatoes, probably in response to changes in the concentrations of linoleic acid. Deletion of SirA and MotA (involved in motility) modestly increased fitness, and deletion of YihT (involved in synthesis of the capsule) contributed to fitness in green but not ripe tomatoes, but interestingly, known Salmonella genes associated with motility and virulence in animals such as hila, flhDC, and fliF did not contribute to the fitness of the bacteria in the fruit (Marvasi et al, 2013; Noel et al, 2010). …”
mentioning
confidence: 99%